ADDRESS TERMS AS MEANS OF EXPRESSION OF POLITENESS IN ENGLISH AND KARAKALPAK LANGUAGES (Konferensiyalar | Conferences, 2024)
In the article, were studied the role of address terms in expressing politeness and compared in English and Karakalpak languages. Address terms, in the context of politeness category have been investigated separately in both cultures, but have not been fully studied in comparison.  The results showed that, address terms play significant role in expressing politeness in social interaction in both languages. To obtain the data were used modern literary works and films.